(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Insurance contract law, which turned 25 years old last October 2006, has experienced some modifications despite of which in some cases it did not managed tokeep pace with the business market evolution and the updating of Spanish insurance industry. However, its technical quality has allowed it to remain in force, since it is based on fundamental insurance principles.This study deals with the insurance contract law and the reforms that would be necessary to carry out from the regulatory, the jurisprudence and the insurance dailypoints of view.